(untitled) (Ascendens Asia Singapore – Bestlink College of the Philippines Journal of Multidisciplinary Research, 2020)
Since the beginning of 1992, the Philippines has been experiencing daily brownout as a result of power shortages. One logical solution to this major problem is to look for non-conventional sources of energy. Battery cells provide a source of power when electricity is not available. Due to high demands, commercial batteries have become expensive. The purpose of this project was to look for ways to develop a cheaper alternative power, namely, a candle lighting battery charger, by using a thermoelectric generator (TEG) as an alternative source of electricity. This study utilized a quantitative experimental research design to test significant difference between the two groups of respondents and between the volts potential in every temperature level (hot and cold) from the candle lighting battery charger by using TEG and to assess the level of acceptability of a developing candle lighting battery charger by using TEG in terms of longevity/life span, volt potential, temperature levels (hot or cold temperature), mechanism, and capacity voltage presentation. The experiment was conducted by doing the following procedures. Prepare all the materials needed. Prepare a can and hold the aluminum plate to absorb heat from candles. To make stands, use bolts and knots between two the cans at a distance of 4 in. Clean the cans by sanding this by using sandpaper. Remove labels with hot water. Drill 18x3=54x6mm holes. Use a file to reduce sharp edges. Heat the can outside by using a candle. Use fine sandpaper or steel wool. Put the bolts into the holes of the aluminum plate and lock it with knots. Put knots again on the bolt. Then, the other aluminum plate should be placed on the top of the knots and lock it again with another knot. Then, place a thermal paste on the top of the aluminum plate and place a TEG. Assemble the electronics. Connect the two cables on the TEG to the USB charging module. Using a soldering iron, screw the cables to the terminal block. Lastly, test the voltage output by a voltmeter at every temperature. The prominent findings of this study are as follows. Electrical engineers very highly accepted the candle lighting battery charger, while the 5th=year Mechanical Engineering students highly accepted the project. The relationship between the volts potential in every temperature level (hot and cold) from the candle lighting battery charger by using TEG was significant. The difference between the assessment of the two groups of respondents on the level of acceptability of candle lighting battery charger by using the TEG in terms of the aforementioned variables was significant. The suggestions forwarded by the two groups of respondents are as follows; use copper, heat sink instead of tin cans to be used on top of TEG and columns for heat balance, refer to different voltages of TEG to add a voltage higher than 5 V, focus on the mechanism for better functioning, add voltage or use another TEG higher than 5 V, and be consistent on some materials and design for a better appearance of the project.